Lymphoepithelial cyst of submandibular gland, a clinical dilemma- case report - Cheereth, Robin; Paulose, Dheeraj Eldho; Ninan, George Abraham (International Surgery Journal, 2017)
Swellings of the head and neck region present great difficulty in accurate diagnosis as well as proper management. Swelling associated with the maxilla and mandible has a tendency to be provisionally diagnosed as orofacial space infections, which is the most common cause for acute swelling in this region. Fine needle aspiration cytology (FNAC), ultrasonogram and computed tomography can be used in supporting diagnosis. It usually occurs due to the process of lymphocyte-induced cystic ductular dilatation and the confirmatory diagnosis is always made postoperatively by histopathological examination. The mainstay in the treatment of a lymphoepithelial cyst remains the surgical approach, which includes complete enucleation of the cyst along with total excision of the involved salivary gland. Here we present an interesting case of swelling in the right submandibular region which was provisionally diagnosed as submandibular space infection, but later proven histopathologically as a lymphoepithelial cyst of the submandibular gland.